Efficacy and safety of dupilumab in patients with uncontrolled severe chronic rhinosinusitis with nasal polyps and a clinical diagnosis of NSAID‐ERD: Results from two randomized placebo‐controlled phase 3 trials. Issue 4 (1st October 2021) - Mullol, Joaquim; Laidlaw, Tanya M.; Bachert, Claus; Mannent, Leda P.; Canonica, G. Walter; Han, Joseph K.; Maspero, Jorge F.; Picado, Cesar; Daizadeh, Nadia; Ortiz, Benjamin; Li, Yongtao; Ruddy, Marcella; et al.
Abstract: Background: About one‐tenth of patients with difficult‐to‐treat chronic rhinosinusitis with nasal polyps (CRSwNP) have comorbid non‐steroidal anti‐inflammatory drug‐exacerbated respiratory disease (NSAID‐ERD). Dupilumab, a fully human monoclonal antibody that blocks the shared interleukin (IL)‐4/IL‐13 receptor component, is an approved add‐on treatment in severe CRSwNP. This post hoc analysis evaluated dupilumab efficacy and safety in patients with CRSwNP with/without NSAID‐ERD. Methods: Data were pooled from the phase 3 SINUS‐24 and SINUS‐52 studies in adults with uncontrolled severe CRSwNP who received dupilumab 300 mg or placebo every 2 weeks. CRSwNP, nasal airflow, lung function, and asthma control outcomes at Week 24 were evaluated, and treatment–subgroup interactions were assessed for patients with and without NSAID‐ERD. Results: Of 724 patients, 204 (28.2%) had a diagnosis of NSAID‐ERD. At Week 24, least squares mean treatment differences demonstrated significant improvements in nasal polyp score, nasal congestion (NC), Lund–Mackay computed tomography, 22‐item Sinonasal Outcome Test (SNOT‐22), Total Symptom Score (TSS), rhinosinusitis severity visual analog scale, peak nasal inspiratory flow (PNIF), six‐item Asthma Control Questionnaire score, and improvement in smell with dupilumab versus placebo (all p < .0001) in patients with NSAID‐ERD. Treatment comparisons demonstrated significantly greater improvements with dupilumab in patients with versus without NSAID‐ERD for NC ( p = .0044), SNOT‐22 ( p = .0313), TSS ( p = .0425), and PNIF ( p = .0123). Conclusions: In patients with uncontrolled severe CRSwNP, dupilumab significantly improved objective measures and patient‐reported symptoms to a greater extent in the presence of comorbid NSAID‐ERD than without. Dupilumab was well tolerated in patients with/without NSAID‐ERD. Abstract : In patients pooled from the SINUS‐24 (NCT02912468) and SINUS‐52 (NCT02898454) studies, patients with CRSwNP and comorbid NSAID‐ERD represent a severe and difficult‐to‐treat population. Improvements in disease control, lung function, and symptom burden were observed with dupilumab treatment versus placebo, irrespective of NSAID‐ERD status. The dupilumab treatment effect was greater in NSAID‐ERD patients for NC, SNOT‐22 total score, TSS, and PNIF. Abbreviations: ACQ‐6, 6‐item asthma control questionnaire; CRSwNP, chronic rhinosinusitis with nasal polyps; FEV1, forced expiratory volume in 1 second; ITT, intent‐to‐treat; LMK‐CT, Lund–Mackay score by computed tomography; NC, nasal congestion; NPS, nasal polyps score; NSAID‐ERD, non‐steroidal anti‐inflammatory drug‐exacerbated respiratory disease; PNIF, peak nasal inspiratory flow; SNOT‐22, 22‐item sinonasal outcome test; TSS, total symptom score; UPSIT, University of Pennsylvania Smell Identification Test; VAS, visual analog scale